Meningkatkan Kemampuan Mengenal Konsep Angka Dengan Media Jam Analog Digital Di Kelompok A Kober Al-Barokah - Jubaedah, Endah; Nurmilah, Siti (Jurnal Pendidikan Islam Anak Usia Dini : Anaking, 2025)
Understanding the concept of numbers for young children is an important aspect of development that needs to be improved because it has a big impact on an individual's survival in the future. In this research, the background is that there are several factors that hinder the introduction of the concept of numbers, namely in the learning process which does not use varied methods and limited learning media, so it is less developed. Researchers encountered a similar problem in Kober Al-Barokah, where children's introduction to the concept of numbers was underdeveloped. Therefore, action needs to be taken to improve children's introduction to the concept of numbers. Researchers are trying to improve the concept of numbers, namely by using digital analog clocks. Digital Analog Clocks are media that can help children to understand the concept of numbers because in these clocks there are several numbers, with various clock media and attractive models it can increase children's interest in learning and children can easily understand each learning activity. The aim of this research is to describe how to improve understanding of the concept of numbers in Kober Al-Barokah, how to apply digital analog clock media in learning environmental themes in Kober Al-Barokah and how to improve children's concept of numbers through digital analog clock media. Apart from that, researchers can find out the extent of the effectiveness of improving children's concept of numbers (variable Y) through digital analog clocks (variable X). The type of research used is classroom action research or PTK with a Kemmis and Taggart design and using qualitative methods with a total of 15 students with 7 male subjects and 8 female subjects. The subjects of this research were group A in Kober Al-Barokah aged 4-5 years. Data collection techniques in this research consist of observation, interviews and documentation. Based on observations that have been made, the concept of early childhood figures in Kober Al-Barokah is 26.6% with the category of children developing according to expectations. When carrying out actions in cycle I there was no improvement because they still used the same media and the percentage results were still 26.6%, in cycle II it increased to 46.6% and cycle III increased to 80% with the category developing very well and 20% with the category developing according to expectations. This shows a significant increase in the introduction of number concepts using digital analog clock media in group A Kober Al-Barokah with a percentage of 100% developing children.  Keywords: Early Childhood, Understanding the Concept of Numbers, Digital Analog Clock